Aqueous liquid coating
Patent Information
- Application Number
- JP2026061129
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-04
- Filing Date
- 2026-04-02
- Publication Date
- 2026-10-16
AI Technical Summary
【0009】 本発明の水性コーティング組成物は、低粘度、良好な塗布特性、及び速硬化特性を有する。本発明の水性コーティング組成物は、非常に高い弾性を示し、かつ、高い伸びにおける高い強さとともに、高い光沢度と、UV、高温及び加水分解などの過酷な周囲条件に対する良好な耐性とを有する。
Smart Images

Figure 2026169194000001 
Figure 2026169194000002 
Figure 2026169194000003
Abstract
Description
TECHNICAL FIELD
[0001] An aqueous liquid coating film that has high strength and high glossiness, does not require a topcoat, and is particularly suitable as a waterproof coating for low-slope roofs.
BACKGROUND ART
[0002] Waterproof liquid coating films are known. For roofing applications, waterproof liquid coating films are used as an alternative to prefabricated sheet membranes for sealing low-slope roofs, which makes application easier, especially for complex roof geometries or for repair purposes, and provides a flexible, seamless roof coating that adheres completely to the substrate. Aqueous products offer the advantage of low viscosity, good fluidity and good workability without the addition of volatile organic solvents. However, such products usually require coating with a topcoat to obtain a tough and resistant finished film surface with high fastness to temperature, UV, hydrolysis and mechanical attack. As a result, the high glossiness of the surface becomes a typical indicator of a surface that is highly durable and has good repellency in terms of dirt adhesion.
[0003] US Patent Application Publication No. 2003 / 0088045 describes a crack-sealing coating system based on polyurethane dispersions suitable for use as floor or roof coatings.
[0004] Aqueous polysiloxane hybrid resins are known to have good weather resistance and good adhesion to various substrates.
PRIOR ART DOCUMENTS
PATENT DOCUMENTS
[0005]
PATENT DOCUMENT 1
SUMMARY OF THE INVENTION
PROBLEMS TO BE SOLVED BY THE INVENTION
[0006] The object of the present invention is to provide an aqueous coating composition suitable for waterproofing low-slope roofs, which has high strength at high elongation and a highly repell surface that does not require a topcoat. [Means for solving the problem]
[0007] Surprisingly, this problem is solved by an aqueous coating composition comprising at least one polyurethane dispersion, at least one polyisocyanate, and at least one polysiloxane hybrid dispersion in the specific ratio described in claim 1.
[0008] Coating compositions based on a combination of polyurethane dispersion and polyisocyanate enable excellent mechanical properties, including very high strength at high elongation and high initial gloss. However, after weathering due to UV, temperature, and humidity, the initial gloss decreases to an undesirable degree. Such surfaces lack sufficient robustness against UV and hydrolysis attacks and require a topcoat. On the other hand, coating compositions based on polysiloxane hybrid dispersion exhibit low strength with minimal or zero elongation. Surprisingly, the combination of the present invention, as can be seen from Table 1 of the experiments, allows for the maintenance of high strength at high elongation and high gloss after weathering tests when the weight ratio of the solid content of the polyurethane dispersion to the solid content of the polysiloxane hybrid dispersion is 25 / 75 to 75 / 25. Outside this ratio range, the mechanical properties are insufficient, or the gloss decreases by an undesirable amount after weathering tests.
[0009] The aqueous coating composition of the present invention has low viscosity, good application characteristics, and rapid curing characteristics. The aqueous coating composition of the present invention exhibits very high elasticity and high strength with high elongation, as well as high gloss and good resistance to harsh ambient conditions such as UV, high temperature, and hydrolysis.
[0010] The aqueous coating composition of the present invention does not require a topcoat and is particularly suitable for waterproofing roofs, terraces, balconies, or facades, and especially for waterproofing low-slope roofs. This significantly reduces time, materials, and labor.
[0011] Other aspects of the present invention are described in other independent claims. Preferred aspects of the present invention are described in dependent claims. [Modes for carrying out the invention]
[0012] The subject of this invention is, - At least one polyurethane dispersion, - At least one polyisocyanate, - At least one polysiloxane hybrid dispersion and This is an aqueous coating composition in which the weight ratio of the solid content of the polyurethane dispersion to the solid content of the polysiloxane hybrid dispersion is 25 / 75 to 75 / 25.
[0013] In this specification, the term "aqueous" means a composition comprising a major polymer as a dispersion or emulsion in water and containing a significant amount of water, typically more than 20% by weight of the total aqueous composition.
[0014] In this specification, the term "polyurethane dispersion" refers to a polyurethane polymer that forms a dispersion with storage stability in water.
[0015] In this specification, the term "polyurethane" encompasses all polymers prepared by the so-called diisocyanate polyaddition method. These polymers may contain other groups, in particular urea groups, in addition to urethane groups.
[0016] As used herein, the term "polysiloxane hybrid dispersion" refers to a hybrid polymer that comprises polysiloxane units and other polymer units different from polysiloxane, and forms a dispersion having storage stability in water.
[0017] As used herein, substance names starting with "poly", such as polyisocyanate and polyol, refer to substances containing two or more of the functional groups appearing in the name.
[0018] As used herein, the term "aliphatic" refers to a substance or polymer that does not contain an aromatic structure. The term "aliphatic" may encompass alicyclic structures.
[0019] The term "storage stability" refers to the ability of a composition to be storable for a period of time, in particular for several months, at room temperature in a suitable watertight container without significant changes in application properties or end-use properties.
[0020] As used herein, the terms "% by weight" or "wt.%" refer to the mass fraction of the constituent component of the composition relative to the entire composition, unless otherwise specified. As used herein, the terms "weight" and "mass" are used synonymously.
[0021] As used herein, "room temperature" refers to a temperature of 23°C.
[0022] All industry standards and norms referred to herein refer to the version in force as of the filing date of the original application, unless otherwise specified.
[0023] Particularly preferred are aliphatic polyether polyurethane dispersions, preferably those having a solids content of 30 to 50% by weight.
[0024] Preferred are anionic polyurethane dispersions, which preferably have carboxylate anions, preferably together with ammonium counterions such as triethylammonium counterions.
[0025] Such polyurethane dispersions are preferably obtained by reacting at least one polyether polyol, at least one carboxylic acid, particularly methylolpropionic acid or methylolbutanoic acid, with at least one aliphatic diisocyanate, such as isophorone diisocyanate, bis(4-isocyanatocyclohexyl)methane, hexane 1,6-diisocyanate, trimethylhexane 1,6-diisocyanate, cyclohexane diisocyanate, or methylcyclohexane diisocyanate, then neutralizing the carboxylic acid group with a suitable neutralizing agent, such as triethylamine, and then dispersing the neutralized isocyanate group-containing polymer in water to extend the chain by reaction of the isocyanate group with a chain extender, such as hydrazine, ethylenediamine, water, or other small molecules having at least two reactive groups selected from primary amine groups, secondary amine groups, and hydroxyl groups.
[0026] The polyurethane dispersion preferably contains several free hydroxyl groups, for example, by using at least one hydroxyl group-containing diamine for chain extension.
[0027] Suitable polyurethane dispersions are commercially available, such as HYDRAN WLS-20 (manufactured by DIC Corporation), or similar polyurethane dispersions from other manufacturers.
[0028] The aqueous coating composition further comprises at least one polyisocyanate. Preferably, it is an aliphatic polyisocyanate, in particular isophorone diisocyanate, bis(4-isocyanatocyclohexyl)methane, hexane 1,6-diisocyanate or 1-methyl-2,4(6)-cyclohexane diisocyanate, and oligomeric forms of these diisocyanates.
[0029] Particularly preferred are oligomers of hexane-1,6-diisocyanate, especially oligomers containing isocyanurate and / or allophanate groups. Such polyisocyanates are liquid at room temperature, are attractive in terms of EHS properties, have moderate reactivity to water, and allow for products with good lightfastness.
[0030] Polyisocyanates may be used as is, or they may be used in a hydrophilic form to obtain good emulsifying properties for use in aqueous compositions. Hydrophilic properties are typically obtained by adding an emulsifier. Such hydrophilic polyisocyanates are commercially available, for example, under the trade names Bayhydur® (manufactured by Covestro) and Bayhydur® Ultra 3100.
[0031] Preferably, the polyisocyanate is a hydrophilic, emulsifiable polyisocyanate.
[0032] The amount of polyisocyanate used in the composition is preferably in balance with the amount of hydroxyl groups that may be present in the polyurethane dispersion. If this is unclear, it can be determined by trying various amounts and judging the properties of the resulting cured composition. Too little polyisocyanate reduces the mechanical properties, while too much polyisocyanate tends to cause the cured composition to exhibit bubbles, and may even become foamed.
[0033] Preferably, the polyisocyanate is used in an amount such that the molar NCO / OH ratio is 0.5 to 1.5, preferably 0.7 to 1.2, and particularly 0.8 to 1.1.
[0034] Preferably, the polyisocyanate is used in such an amount that the weight ratio of the polyisocyanate to the solid content of the polyurethane dispersion is 70 / 30 to 92 / 8.
[0035] Preferably, the aqueous coating composition contains 3 to 20 parts by weight, preferably 5 to 15 parts by weight, of polyisocyanate per 100 parts by weight of the total solid content of the polyurethane dispersion and the polysiloxane hybrid dispersion. Such a coating composition has good mechanical properties in terms of high tensile strength and high elongation.
[0036] The aqueous coating composition further comprises at least one polysiloxane hybrid dispersion.
[0037] Preferably, the polysiloxane hybrid dispersion has a solid content of 30 to 50% by weight.
[0038] Preferably, the polysiloxane hybrid dispersion has a polysiloxane content of 20 to 35% by weight relative to the total solid content of the polysiloxane hybrid dispersion.
[0039] Preferably, the polysiloxane hybrid dispersion is a polysiloxane-acrylic hybrid dispersion, and the polysiloxane-acrylic hybrid dispersion is preferably urethane-modified.
[0040] Such aqueous hybrid dispersions are commercially available, for example, as CERANATE WHW-822 or CERANATE WSA-1080 (both manufactured by DIC Corporation). CERANATE WHW-822 is particularly preferred.
[0041] The polysiloxane hybrid dispersion is used in quantities such that the weight ratio of the solid content of the polyurethane dispersion to the solid content of the polysiloxane hybrid dispersion is in the range of 25 / 75 to 75 / 25. This allows for an attractive combination of high strength, high elongation, and high gloss after weather resistance testing of the cured coating.
[0042] Particularly preferred is a weight ratio of the solid content of the polyurethane dispersion to the solid content of the polysiloxane hybrid dispersion of 40 / 60 to 70 / 30, preferably 50 / 50 to 70 / 30, and especially 55 / 45 to 65 / 35. Such a coating composition has a particularly attractive combination of high strength, high elongation, and high gloss after weather resistance testing of the cured coating, and this combination makes it possible to use it in highly durable waterproofing systems without the application of a topcoat.
[0043] The aqueous coating composition may contain further components.
[0044] Appropriate additional ingredients are especially, - Fillers, for example, crushed or precipitated calcium carbonate (chalk), optionally coated with fatty acids, such as stearate; barium sulfate (barite); slate; silicate (quartz); magnesium silicate (talc); aluminosilicate (clay, kaolin); dolomite; mica; glass bubbles; silicic acid, especially fumed silica; carbon black; graphite; microspheres; calcium oxide; calcium hydroxide; aluminum oxide; aluminum hydroxide; magnesium oxide; magnesium hydroxide or zinc oxide. - Pigments, especially titanium dioxide, iron oxide, or organic pigments, - Further polymer dispersions, such as acrylic dispersions, - Adhesion promoters, especially organic alkoxysilanes, oligomer silanes, or titanates, - Fibers, especially glass fibers, carbon fibers, metal fibers, ceramic fibers, plastic fibers, especially polyamide fibers or polyethylene fibers, or natural fibers, such as wool, cellulose, hemp or sisal, - Nanofibers, such as graphene or carbon nanotubes, - dye, - Organic solvents, - Plasticizers or film-forming aids, especially phthalates, hydrogenated phthalates, terephthalates, hydrogenated terephthalates, trimellitates, adipates, azelates, sebacates, citrates, benzoates, glycol ethers, glycol esters, polyether polyols, organic sulfonates or phosphates, polybutenes, polyisobutenes, or epoxidized soy or linseed oil. - Thickening agents, such as bentonite, castor oil derivatives, hydrogenated castor oil, polyamides, polyamide waxes, polyurethanes, urea compounds, fumed silica, cellulose ethers, or hydrophobic modified polyoxyethylenes. - Further additives, such as surfactants, wetting agents, defoamers, flow improvers, leveling agents, degassing agents, matting agents, antioxidants, biocides, or stabilizers against UV or heat. That is the case.
[0045] Preferably, the aqueous coating composition further contains at least one pigment, preferably titanium dioxide, in an amount of 10 to 50 parts by weight, preferably 20 to 30 parts by weight, per 100 parts by weight of the total solid content of the polyurethane dispersion and the polysiloxane hybrid dispersion.
[0046] Preferably, the aqueous coating composition further comprises at least one surfactant, wetting agent, or defoaming agent.
[0047] Preferably, the aqueous coating composition further comprises at least one thickening agent.
[0048] Preferably, the aqueous coating composition contains an organic solvent with a boiling point of less than 250°C at atmospheric pressure in an amount of less than 5% by weight, more preferably less than 2% by weight, and particularly less than 1% by weight, relative to the total aqueous coating composition.
[0049] In one preferred embodiment of the present invention, the aqueous coating composition is - A first component comprising a polyurethane dispersion, a polysiloxane hybrid dispersion, and optionally further components, preferably selected from titanium dioxide, surfactants, wetting agents, defoaming agents and thickeners, and - A second component containing or consisting of polyisocyanate Includes.
[0050] Further components may be part of the first component and / or part of the second component, or may be packaged as further components to be added to the aqueous coating composition at the time of use. Further components that are reactive to isocyanate groups are preferably included in the first component, while further components that are sensitive to moisture are preferably included in the second component.
[0051] The first and second components are packaged separately in watertight containers. The separated first and second components each have good storage stability. At the time of use, the first and second components are mixed together, and the mixed composition is applied. The mixing ratio of the first and second components is preferably such that the amount of isocyanate groups in the second component is in an appropriate ratio to the hydroxyl groups contained in the first component. The NCO / OH molar ratio is preferably 0.5 to 1.5, more preferably 0.7 to 1.2, and particularly preferably 0.8 to 1.1.
[0052] Typically, the mixing ratio of the first component to the second component is 2 / 1 to 100 / 1, preferably 5 / 1 to 50 / 1, and particularly 10 / 1 to 40 / 1.
[0053] A further subject of the present invention is the use of aqueous coating compositions for waterproofing roofs, terraces, balconies, or facades, particularly for waterproofing low-slope roofs.
[0054] Further subject matter of the present invention is i) A step of mixing the components of the aqueous coating composition to obtain a macroscopically homogeneous fluid, ii) The mixed coating composition is distributed at a rate of 0.3 to 1.2 kg / m². 2 Preferably 0.4 to 1.0 kg / m2 , more preferably 0.4 to 0.8 kg / m 2 The process involves applying an amount to the substrate, followed by iii) A step of curing the applied coating under ambient conditions by evaporation of volatile components and reaction of isocyanate groups, iv) Optionally, a process in which steps i), ii), and iii) are repeated. This is a coating method that includes [a specific component].
[0055] The mixing process can be carried out by any suitable method, preferably using a propeller-type agitator or similar device.
[0056] The mixed composition preferably has self-leveling properties and low viscosity.
[0057] The mixed composition is preferably applied to the substrate, preferably the surface of a roof, terrace, balcony, or facade, using a brush, roller, or spraying device.
[0058] The applied composition hardens by evaporation of volatile components, mainly water, and by the reaction of isocyanate groups with hydroxyl groups, particularly those present in the polyurethane dispersion. Additional isocyanate groups can react with water and other reactive components that may be present in the composition.
[0059] Curing is typically carried out under ambient conditions, preferably at 5-40°C, more preferably at 10-30°C.
[0060] After curing, a second layer and possibly a third layer are preferably applied to finally obtain the desired thickness of the cured coating.
[0061] A two-layer coating process is preferred.
[0062] The cured coating is obtained by the coating method described.
[0063] The cured coating preferably has a layer thickness of 0.2 to 2 mm, preferably 0.3 to 1.5 mm, and particularly 0.4 to 1 mm. The cured coating exhibits extremely high elasticity and high strength with high elongation, along with high gloss and good resistance to harsh ambient conditions such as UV, high temperatures, and hydrolysis.
[0064] Preferably, the cured coating has a tensile strength of at least 10 MPa, preferably at least 15 MPa, and particularly at least 20 MPa, measured in accordance with JIS A 6021 using a dumbbell-shaped test specimen with a thickness of 0.4 mm, a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm, at a crosshead speed of 500 mm / min after curing for 7 days in a standard climate.
[0065] Preferably, the cured coating has an elongation at break of at least 100%, preferably at least 150%, and particularly at least 200%, measured in accordance with JIS A 6021 using a dumbbell-shaped test specimen with a thickness of 0.4 mm, a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm, at a crosshead speed of 500 mm / min after curing for 7 days in a standard climate.
[0066] Preferably, the cured coating has a 60° gloss of at least 50%, preferably at least 55%, more preferably at least 60%, measured at a 60° angle in accordance with JIS K 5600-4-7 using a VG 8000 gloss meter manufactured by Nippon Denshoku Industries Ltd., after exposure to a 1000-hour accelerated weathering test using an EYE Super UV Tester manufactured by Iwasaki Electric Co., Ltd., with a thickness of 0.4 mm and a square test piece measuring 60 × 60 mm.
[0067] In particular, hardened coatings - After curing for 7 days in a standard climate, a dumbbell-shaped test specimen with a thickness of 0.4 mm, a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm was measured in accordance with JIS A 6021 at a crosshead speed of 500 mm / min, and the tensile strength was at least 10 MPa, preferably at least 15 MPa, and particularly at least 20 MPa. - After curing for 7 days in a standard climate, the elongation at break of at least 100%, preferably at least 150%, and especially at least 200% was measured in accordance with JIS A 6021 using a dumbbell-shaped test specimen with a thickness of 0.4 mm, a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm, at a crosshead speed of 500 mm / min. It holds.
[0068] Most preferably, the cured coating is - After curing for 7 days in a standard climate, the tensile strength was measured in accordance with JIS A 6021 at a crosshead speed of 500 mm / min using a dumbbell-shaped test specimen with a thickness of 0.4 mm, a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm, with a tensile strength of at least 10 MPa, preferably at least 15 MPa, and particularly at least 20 MPa. - After curing for 7 days in a standard climate, the elongation at break of at least 100%, preferably at least 150%, and especially at least 200% was measured in accordance with JIS A 6021 using a dumbbell-shaped test specimen with a thickness of 0.4 mm, a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm, at a crosshead speed of 500 mm / min. - And, using a 0.4 mm thick, 60 x 60 mm square test specimen, after exposure to a 1000-hour accelerated weathering test using an EYE Super UV Tester manufactured by Iwasaki Electric Co., Ltd., with UV, temperature, and humidity, the 60° gloss was measured at a 60° angle in accordance with JIS K 5600-4-7 using a gloss meter VG 8000 manufactured by Nippon Denshoku Industries Co., Ltd., with a gloss of at least 50%, preferably at least 55%, more preferably at least 60%. It holds.
[0069] These properties make hardened coatings particularly suitable as part of a waterproofing system to protect low-slope roofs.
[0070] Another subject of the present invention is, - Optionally, include a primer and / or undercoat, - The described cured coating is preferably included in a layer thickness of 0.2 to 2 mm, preferably 0.3 to 1.5 mm, and particularly 0.4 to 1 mm. It is a waterproof system. [Examples]
[0071] The following examples illustrate the present invention without limiting it.
[0072] "Standard climate" refers to a temperature of 23±1℃ and a relative atmospheric humidity of 50±5%.
[0073] [Table 1]
[0074] Coating composition: Examples E1~E9: For each example, the components shown in Table 1 or 2 were mixed in a given amount (parts by weight) to prepare the first component, which was then stored in a watertight container.
[0075] As the second component, polyisocyanate is used in the amount (parts by weight) shown in Table 1 or 2.
[0076] Before use, the second component was mixed with the first component to form a macroscopically homogeneous liquid, and this mixed composition was then immediately tested as described below.
[0077] A first layer of the mixed composition is applied to a Teflon® coated sheet at a rate of 0.6 kg / m². 2 Apply the mixture in the specified amount, and then, after the first layer has cured for 24 hours in a standard climate, apply the second layer of the mixed composition at a rate of 0.6 kg / m². 2Each example of a cured film was prepared with a thickness of 0.4 mm by applying the specified amount onto the first layer. After drying for a further 96 hours in a standard climate, the film was removed from the Teflon® coated sheet, inverted, and cured for a further 72 hours in a standard climate before conducting the following tests.
[0078] Tensile strength and elongation at break were measured in accordance with JIS A 6021 using dumbbell-shaped test specimens punched out from a cured film, with a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm, at a crosshead speed of 500 mm / min.
[0079] Tear strength was measured using angle-shaped test pieces punched from the cured film at a crosshead speed of 500 mm / min in accordance with JIS A 6021.
[0080] The 60° gloss was measured using a 60 x 60 mm square test piece cut from a cured film, at a 60° angle in accordance with JIS K 5600-4-7, using a VG 8000 gloss meter manufactured by Nippon Denshoku Industries Ltd. After the initial measurement, the test piece was subjected to a 1000-hour accelerated weathering test using an EYE Super UV Tester manufactured by Iwasaki Electric Co., Ltd., under UV, temperature, and humidity, followed by further gloss measurements.
[0081] The results are shown in Table 1 or 2.
[0082] References are indicated with "(Ref.)".
[0083] [Table 2]
[0084] Table 1 shows that Examples E3 to E6 of the present invention exhibited high strength with high elongation, as well as high gloss after 1000 hours of UV exposure, which is particularly true for preferred Examples E4 and E5. Reference Examples E1 and E2, which did not contain or contained insufficient polysiloxane hybrid dispersion, exhibited insufficient gloss after UV exposure, while Reference Example E7, which did not contain polyurethane dispersion, exhibited insufficient low strength and elongation.
[0085] [Table 3]
[0086] Table 2 shows that Example E8 of the present invention exhibited high strength with good elongation, as well as high gloss after 1000 hours of UV exposure, whereas Reference Example E9, which did not contain a polyurethane dispersion, exhibited insufficient low strength and elongation.
[0087] A comparison of Example E4 and Example E8 shows that the urethane-modified polysiloxane-acrylic hybrid dispersion (S1) of Example E4 enables higher tensile strength, elongation, and tear strength compared to the non-urethane-modified polysiloxane-acrylic hybrid dispersion (S2) of Example E8.
Claims
1. - At least one polyurethane dispersion, - At least one polyisocyanate, - At least one polysiloxane hybrid dispersion and an aqueous coating composition comprising, An aqueous coating composition wherein the weight ratio of the solid content of the polyurethane dispersion to the solid content of the polysiloxane hybrid dispersion is 25 / 75 to 75 / 25.
2. The aqueous coating composition according to claim 1, wherein the polyurethane dispersion is an aliphatic polyether polyurethane dispersion, preferably with a solid content of 30 to 50% by weight.
3. The aqueous coating composition according to claim 1 or 2, wherein the polyisocyanate is an oligomer of hexane-1,6-diisocyanate.
4. The aqueous coating composition according to any one of claims 1 to 3, wherein the coating composition contains 3 to 20 parts by weight, preferably 5 to 15 parts by weight, of the polyisocyanate per 100 parts by weight of the total solid content of the polyurethane dispersion and the polysiloxane hybrid dispersion.
5. The aqueous coating composition according to any one of claims 1 to 4, wherein the weight ratio of the solid content of the polyurethane dispersion to the polyisocyanate is 70 / 30 to 92 / 8.
6. The aqueous coating composition according to any one of claims 1 to 5, wherein the polysiloxane hybrid dispersion has a solid content of 30 to 50% by weight.
7. The aqueous coating composition according to any one of claims 1 to 6, wherein the polysiloxane hybrid dispersion is a polysiloxane-acrylic hybrid dispersion.
8. The aqueous coating composition according to claim 7, wherein the polysiloxane-acrylic hybrid dispersion is urethane-modified.
9. The aqueous coating composition according to any one of claims 1 to 8, wherein the weight ratio of the solid content of the polyurethane dispersion to the solid content of the polysiloxane hybrid dispersion is 40 / 60 to 70 / 30, preferably 50 / 50 to 70 / 30, and particularly 55 / 45 to 65 / 35.
10. The aqueous coating composition according to any one of claims 1 to 9, wherein the aqueous coating composition further comprises at least one pigment, preferably titanium dioxide, in an amount of 10 to 50 parts by weight, preferably with respect to 100 parts by weight of the total solid content of the polyurethane dispersion and the polysiloxane hybrid dispersion.
11. - A first component comprising the polyurethane dispersion, the polysiloxane hybrid dispersion, and optionally further components, preferably selected from titanium dioxide, surfactants, wetting agents, and defoaming agents, and - A second component comprising or consisting of the polyisocyanate. An aqueous coating composition according to any one of claims 1 to 10, comprising:
12. Use of the aqueous coating composition according to any one of claims 1 to 11 for waterproofing roofs, terraces, balconies or facades, and especially for waterproofing low-slope roofs.
13. i) A step of mixing the components of the aqueous coating composition according to any one of claims 1 to 12 to obtain a macroscopically homogeneous fluid, ii) The mixed coating composition is distributed at a rate of 0.3 to 1.2 kg / m². 2 Preferably 0.4 to 1.0 kg / m 2 , more preferably 0.4 to 0.8 kg / m 2 The process involves applying an amount to the substrate, followed by iii) A step of curing the applied coating under ambient conditions by evaporation of volatile components and reaction of isocyanate groups, iv) A process in which steps i), ii), and iii) are arbitrarily repeated. A coating method including
14. A cured coating obtained by the coating method described in claim 13, - After curing for 7 days in a standard climate, a tensile strength of at least 10 MPa, preferably at least 15 MPa, and especially at least 20 MPa was measured in accordance with JIS A 6021 at a crosshead speed of 500 mm / min using a dumbbell-shaped test specimen with a thickness of 0.4 mm, a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm, - After curing for 7 days in a standard climate, a dumbbell-shaped test specimen with a thickness of 0.4 mm, a length of 100 mm, a bridge length of 20 mm, and a bridge width of 5 mm was measured at a crosshead speed of 500 mm / min in accordance with JIS A 6021, showing an elongation at break of at least 100%, preferably at least 150%, and particularly at least 200%. A hardened coating having the following properties.
15. - Optionally, include a primer and / or undercoat, - A waterproofing system comprising the cured coating according to claim 13 or 14, preferably in a layer thickness of 0.2 to 2 mm, preferably 0.3 to 1.5 mm, and particularly 0.4 to 1 mm.
Citation Information
Patent Citations
Use of aqueous polyurethane dispersions in formulations for crack sealing coating systems
US20030088045A1